Pengaruh penerapan model pembelajaran Auditory Intellectually Repetition (AIR) terhadap kemampuan berpikir tingkat tinggi peserta didik - Alpian Alpian (Universitas Riau Kepulauan, 2022)
This study aims to obtain information about whether or not there is an influence in the application of the Auditory Intellectually Repetition (AIR) learning model on the higher-order thinking skills of students on the motion system material. This research was conducted in class XI SMA N 1 Tanjung Batu. The method used in this research is Quasi Experimental with the research design of Nonequivalent Control Group Design. In determining the research sample using purposive sampling, namely obtained samples in class XI. IPA 3 which acts as an experimental class with a total of 32 students while acting as a control class is a class XI IPA 4 with a total of 31 students. The method used in data collection is a test of higher order thinking skills and activity observation. Repetition has a significant effect on students' Higher-Level thinking skills in the movement system material for class XI IPA 3 SMA Negeri 1 Tanjung Batu. Keywords: Auditory Intellectually Repetition Model, Higher Order Thinking, Movement System.